2002
DOI: 10.1046/j.1439-0523.2002.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for resistance to lentil Ascochyta blight

Abstract: Ascochyta blight, caused by Ascochyta lentis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 38 publications
0
33
0
2
Order By: Relevance
“…Sources of partial resistance have been identified in all of the cool season food legumes and the currently available resistance is being used in breeding programmes designed to develop cultivars with improved resistance. Since there are some recent reviews on breeding methods, screening procedures, the ascochyta diseases and biology of the pathogens (Bretag et al 2006;Pande et al 2005;Tivoli et al 2006;Torres et al 2006;Ye et al 2002), we will in this review mainly focus on the recent developments in understanding the genetics of host resistance for each of the major cool season food legumes and point out immediate needs in research that in our opinion will further advance deployment of resistance in managing ascochyta blight in cool season food legumes.…”
Section: Introductionmentioning
confidence: 99%
“…Sources of partial resistance have been identified in all of the cool season food legumes and the currently available resistance is being used in breeding programmes designed to develop cultivars with improved resistance. Since there are some recent reviews on breeding methods, screening procedures, the ascochyta diseases and biology of the pathogens (Bretag et al 2006;Pande et al 2005;Tivoli et al 2006;Torres et al 2006;Ye et al 2002), we will in this review mainly focus on the recent developments in understanding the genetics of host resistance for each of the major cool season food legumes and point out immediate needs in research that in our opinion will further advance deployment of resistance in managing ascochyta blight in cool season food legumes.…”
Section: Introductionmentioning
confidence: 99%
“…(Bayaa et al 1994 ). Ye et al ( 2002 ) listed a series of cultivated and wild lentil materials as sources of partial resistance to Ascochyta blight, and Muehlbauer and Chen ( 2007 ) reported that the most prominent among the partially resistant germplasm accessions consisted of lentil accessions PI 339283, PI 374118, ILL5588, ILL5684, PR86-360, and ILL7537. Wild materials have also been used as a source of genes for winter hardiness.…”
Section: Germplasm Collectionmentioning
confidence: 99%
“…Host inoculations of these fungi demonstrated that they were host-specifi c, causing disease only on the host species from which they were isolated (Hernández-Bello et al 2006 ;Peever 2007 ). Tivoli et al ( 2006 ) provided a thorough review on the sources of resistance and screening techniques for Ascochyta blight in lentil, and Ye et al ( 2002 ) gave an account of suitable breeding techniques for the selection of lentils with resistance to Ascochyta blight; partial resistance to the disease is available in germplasm (Muehlbauer and Chen 2007 ).…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation
“…In lentil, attempts have been made to transfer the alien genes from L. lamottei and L. nigricans to Lens culinaris using L. ervoides as a bridge species along with embryo rescue technique. This offers the possibility of transferring the genes for resistance to ascochyta blight and anthracnose to L. culinaris and broadening the resistance gene base in the cultivated species (Ye et al 2002 ;Tullu et al 2006 ).…”
Section: Use Of Bridge Speciesmentioning
confidence: 99%